OBIC technique applied to wide bandgap semiconductors from 100 K up to 450 K. (5th April 2017) - Hamad, H; Planson, D; Raynaud, C; Bevilacqua, P
Abstract: Wide bandgap semiconductors have recently become more frequently used in the power electronics domain. They are predicted to replace traditional silicon, especially for high voltage and/or high frequency devices. Device design has made a lot of progress in the last two decades. Substrates up to six inches in diameter have now been commercialized with very low defect densities. Such a development is due to continuous studies. Of these studies, those that allow an excess of charge carriers in the space charge region (like OBIC - optical beam induced current, and EBIC - electron beam induced current) are useful to analyze the variation of electric field as a function of the voltage and the beam position. This paper shows the OBIC technique applied to wide bandgap semiconductor-based devices. OBIC cartography gives an image of the electric field in the device, and the analysis of the OBIC signal helps one to determine some characteristics of the semiconductors, like minority carrier lifetime and ionization rates. These are key parameters to predict device switching behavior and breakdown voltage.